DDX60L is an interferon-stimulated gene product restricting hepatitis C virus replication in cell culture - Grünvogel, Oliver; Esser-Nobis, Katharina; Reustle, Anna; Schult, Philipp; Müller, Birthe; Metz, Philippe; Trippler, Martin; Windisch, Marc Peter; Frese, Michael; Binder, Marco; Fackler, Oliver Till; Bartenschlager, Ralf; et al. (Journal of virology, 2015)
All major types of interferon (IFN) efficiently inhibit hepatitis C virus (HCV) replication in vitro and in vivo. Remarkably, HCV replication is not sensitive to IFN-γ in the hepatoma cell line Huh6, despite an intact signaling pathway. We performed transcriptome analyses between Huh6 and Huh-7 cells to identify effector genes of the IFN-γ response and thereby identified the DExD/H box helicase DEAD box polypeptide 60-like (DDX60L) as a restriction factor of HCV replication. DDX60L and its homolog DEAD box polypeptide 60 (DDX60) were both induced upon viral infection and IFN treatment in primary human hepatocytes. However, exclusively DDX60L knockdown increased HCV replication in Huh-7 cells and rescued HCV replication from type II IFN as well as type I and III IFN treatment, suggesting that DDX60L is an important effector protein of the innate immune response against HCV. In contrast, we found no impact of DDX60L on replication of hepatitis A virus. DDX60L protein was detectable only upon strong ectopic overexpression, displayed a broad cytoplasmic distribution, but caused cytopathic effects under these conditions. DDX60L knockdown did not alter interferon-stimulated gene (ISG) induction after IFN treatment but inhibited HCV replication upon ectopic expression, suggesting that it is a direct effector of the innate immune response. It most likely inhibits viral RNA replication, since we found neither impact of DDX60L on translation or stability of HCV subgenomic replicons nor additional impact on assembly of infectious virus. Similar to DDX60, DDX60L had a moderate impact on RIG-I dependent activation of innate immunity, suggesting additional functions in the sensing of viral RNA. - IMPORTANCE Interferons induce a plethora of interferon-stimulated genes (ISGs), which are our first line of defense against viral infections. In addition, IFNs have been used in antiviral therapy, in particular against the human pathogen hepatitis C virus (HCV); still, their mechanism of action is not well understood, since diverse, overlapping sets of antagonistic effector ISGs target viruses with different biologies. Our work identifies DDX60L as a novel factor that inhibits replication of HCV. DDX60L expression is regulated similarly to that of its homolog DDX60, but our data suggest that it has distinct functions, since we found no contribution of DDX60 in combatting HCV replication. The identification of novel components of the innate immune response contributes to a comprehensive understanding of the complex mechanisms governing antiviral defense.
Accepted manuscript posted online 12 August 2015
Gesehen am 13.01.2021